2021
DOI: 10.3991/ijet.v16i03.17889
|View full text |Cite
|
Sign up to set email alerts
|

Game Technologies to Assist Learning of Communication Skills in Dialogic Settings for Persons with Aphasia

Abstract: Persons with aphasia suffer from a loss of communication ability as a consequence of a brain injury. While rare, a small strand of research indicates effectiveness of dialogic interventions for communication development for persons with aphasia, but a vast amount of research studies shows its effectiveness for other target groups. In this paper, we describe the main parts of the hitherto technological development of an application named Dialogica that is (i) aimed at facilitating increased communicative partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Also applied to math teaching, it is confirmed by Wahidah et al that using digital games to design multimedia confirmed not only helps learners remember and read, but also helps learners participate in the process of finding concepts. The learning process is fun and interactive [36]. An area related to language teaching has also produced positive results using digital games, such as research report of Backman et al, based on computer game technology as well as in dialogue education theory and debate theory, the effectiveness of dialogue interventions to develop communication for people with aphasia has been improved [37].…”
Section: The Efficiency Criteria Of Digital Game-based Instructional Technologymentioning
confidence: 99%
“…Also applied to math teaching, it is confirmed by Wahidah et al that using digital games to design multimedia confirmed not only helps learners remember and read, but also helps learners participate in the process of finding concepts. The learning process is fun and interactive [36]. An area related to language teaching has also produced positive results using digital games, such as research report of Backman et al, based on computer game technology as well as in dialogue education theory and debate theory, the effectiveness of dialogue interventions to develop communication for people with aphasia has been improved [37].…”
Section: The Efficiency Criteria Of Digital Game-based Instructional Technologymentioning
confidence: 99%
“…One attempt at developing a tool to provide this support is an app prototype called Dialogica, a networked multiuser application, designed for large screen mobile devices, that is "intended to provide opportunities for [persons with aphasia] to participate actively in conversations about contestable questions and assist [them] in expressing themselves […] through personal avatars, animations and chats" (Backman et al, 2021, p. 195-6). It features several tools and functions specifically designed to support persons with communication disorders in participating actively and qualitatively in philosophical dialogues, such as text-to-speech technology and informative symbols to accompany text, but also advanced tools built upon theory and methodology from P4wC and argumentation analysis, such as a palette of dialogic moves and a "conversation tree" (Backman et al, 2021). Dialogica is intended to aid interactional symmetry, acknowledgement of participants' contributions in the dialogues, and multi-modal communication through both verbal and visual expressions (Backman et al, 2021).…”
Section: Dialogicamentioning
confidence: 99%
“…It features several tools and functions specifically designed to support persons with communication disorders in participating actively and qualitatively in philosophical dialogues, such as text-to-speech technology and informative symbols to accompany text, but also advanced tools built upon theory and methodology from P4wC and argumentation analysis, such as a palette of dialogic moves and a "conversation tree" (Backman et al, 2021). Dialogica is intended to aid interactional symmetry, acknowledgement of participants' contributions in the dialogues, and multi-modal communication through both verbal and visual expressions (Backman et al, 2021). Such characteristics have been found to positively influence active participation of persons with aphasia in prior research (Lee & Azios, 2020).…”
Section: Dialogicamentioning
confidence: 99%